Designing and evaluating the technical, economic and environmental performance of an adsorption cooling system operating using bioresources from waste streams of mango processing - Dzigbor, Aaron (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.